An Exploratory Investigation of Organizational Climate and Job Satisfaction in a Hospital - Lyon, Herbert L.; Ivancevich, John M. (Academy of Management Journal, 1974)
The organizational climate of a hospital is investigated, and its impact on job satisfaction is analyzed for nurses and administrators. Different climate dimensions are found to influence individual job satisfaction facets for nurses and administrators, and the impact of organizational climate on satisfaction varies with the climate dimension and the type of satisfaction.